PENGUJIAN SINKING SPEED SERAT ALAMI - Muhammad Agam Thahir; Irwandy Syofyan; Isnaniah Isnaniah (Universitas Teuku Umar, 2017)
The aim of this study to determine the elongation of three types of natural fibers. The method used is an experiment, by directly testing samples of the rope in the aquarium. Sinking speed value of banana stem fiber is 4.8 cm / sec, pandan leaves 3.9 cm / sec, bundung grass fibers 2.6 cm / sec. The third of these natural fibers, banana stem fibers that have the potential as for natural fibre rope material fishing gear.